Halal food perception, practices and preferences of selected Muslim communities in Metro Manila - Banares, Elaine Lorilla (2012)
This study looked into halal food in the Philippines based on the perception, practices, and food preferences of selected Muslim communities in Metro Manila. It is premised on the fact that while Philippines has a sizeable population of Muslims, there is a lack of standard definition of what constitutes halal food. This study is in support of the ongoing attempt by the various bodies including government agencies to standardize the definition of halal food. The research method is a descriptive survey using purposive sampling to arrive at a number of respondents who were categorized as either "Halal-learned" or "General Muslims." The findings revealed that both categories of respondents find that Muslim food is synonymous with halal food. Cleanliness and sanitation ranks first in the factors to be considered when dining out. Naturally-grown foods do not need to be halal-certified. In contrast, baked products, processed foods and especially meats need certification and should pass through the "halal highway" to ensure that these products are not mixed with haram to avoid contamination. Chi-Square Goodness of Fit value at p<0.05 was used to assess significant coincidence. Both groups of respondents coincided significantly in considering religion as the foremost factor that affects their food preferences. Part of the study's conclusion and recommendation was the need for a broader understanding of what constitutes halal and a standard definition would be a great help to business and culutral understanding.